Estimating the demand function for electrical services for the family sector in Erbil governorate (Raparin Journal of Humanities (RJH), 2023)
This study aimed to estimate the function of demand for electric energy in the domestic sector in the Erbil governorate for the year 2022. The importance of the study comes from the fact that electric power is of great importance in the domestic sector, The electrical sector has an impact on all different areas of life. And by showing the factors affecting the increase in the demand for domestic electricity, where the domestic sector is one of the most important and most consumers of electric energy. The study relied on the deductive approach to study the determinants of demand for household electrical energy by collecting data through a questionnaire for a sample of families in Erbil governorate. And then using standard models to determine the quantitative relationship between expenditure on household electrical energy with its determinants. The study reached a number of conclusions, including: The results of estimating the determinants of demand for electrical energy in Erbil governorate are (monthly income, number of family members, housing area, educational level, presence of students in the family, number of appliances in the house, working hours Appliances in the house, the mechanism of confrontation against the separation of electrical loads, the determining factors for reducing the demand for electricity), where the estimated coefficients signals were in agreement with the economic theory and at high levels of significance. The study concluded with a number of proposals, including: rationalizing the consumption of electrical energy by using mechanisms, spreading awareness and increasing the consumption culture among members of society. Work on the commitment to pay the monthly bills, In addition to paying the accumulated bills, Using legitimate electricity and not working on electricity theft, Interest by the government and families in using renewable energy such as solar panels and wind turbines.